PENGARUH PAJAK, EXCHANGE RATE, TUNNELING INCENTIVE, DAN LEVERAGE TERHADAP TRANSFER PRICING - Bela Pratiwi (Jurnal Ekonomi dan Bisnis, 2018)
This study aims to determine the effect of tax, Exchange rate, tunneling incentive, and leverageto Transfer Pricing. Dependent variable in this study is Transfer Pricing which is proxied withthe value from a related party transaction (RPT) of sale. The independent variables in this studyare tax, Exchange rate, tunneling incentive, and leverage. This study took the secondary datain financial statements or annual reports that have been published by companies in IndonesiaStock Exchange. The population in this study are all the manufacturing companies listed on theIndonesia Stock Exchange in 2012-2016. This study took manufacturing companies listed on theIndonesia Stock Exchange as sample, especially the various industry sectors from years 2012-2016. Sampling technique used in this study was purposive sampling method. The total numberof sample in this study is 35 firm years from seven companies. The analytical method used waslogistic regression analysis using SPSS program version 16. The results of the analysis inthis study indicate that tax, Exchange rate, and tunneling incentive have no significant effect onTransfer Pricing, whereas leverage has a significant positive effect on Transfer Pricing.Keywords: Transfer Pricing, Tax, Exchange rate, Incentive Tunneling, Leverage.